A mini-review on coal fly ash properties, utilization and synthesis of zeolites. Issue 7 (3rd July 2022) - Tauanov, Zhandos; Azat, Seitkhan; Baibatyrova, Aknur
ABSTRACT: Coal fly ash is considered as a by-product of coal combustion power stations that may pertain unique properties and utilization fields. This review article gives an overview of different classification methods with comparative data on the chemical composition of coal and coal fly ash. Furthermore, a review describes in detail the utilization sectors of coal fly ash that expands from environmental application to materials production and possible recovery of precious elements. A particular interest is set on the synthesis of zeolites by applying modern production approaches along with state-of-the-art application fields starting from heavy metal removal to catalysis. It suggests to consider different methods of synthesis of zeolites by highlighting the main drawbacks and advantages.